2016
DOI: 10.1002/ange.201603648
|View full text |Cite
|
Sign up to set email alerts
|

A Single Methylene Group in Oligoalkylamine‐Based Cationic Polymers and Lipids Promotes Enhanced mRNA Delivery

Abstract: Supportinginformation and the ORCID identification number(s) for the author(s) of this article can be found under http://dx. Communications 9591Angew.C hem. Int.E d. 2016, 55,9 591 -9595 2 016 Wiley-VCH VerlagG mbH &C o. KGaA,W einheim

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 18 publications
0
33
0
Order By: Relevance
“…Cell-and tissue-specific delivery of cmRNA is currently considered a major obstacle to overcome for RTT. 26 We could show that intravenous delivery of reporter cmRNA in LLF as described by Jarzębi nska et al 35 led to strong and liver-specific protein translation ( Figures 4A and 4B). Immunohistochemical stainings indicate that intravenous application is a potent delivery mechanism for reaching a high number of hepatocytes, which was previously shown for delivery of small interfering RNA (siRNA) as well as mRNA.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Cell-and tissue-specific delivery of cmRNA is currently considered a major obstacle to overcome for RTT. 26 We could show that intravenous delivery of reporter cmRNA in LLF as described by Jarzębi nska et al 35 led to strong and liver-specific protein translation ( Figures 4A and 4B). Immunohistochemical stainings indicate that intravenous application is a potent delivery mechanism for reaching a high number of hepatocytes, which was previously shown for delivery of small interfering RNA (siRNA) as well as mRNA.…”
Section: Discussionmentioning
confidence: 56%
“…Dysregulation of the local RAS contributes significantly to inflammation and fibrosis, 44,45 a process that can best be counterbalanced by specific ACE2 translation in the affected organs. For the purpose of liver-targeted cmRNA delivery, we chose lipoplexes (referred to as the liver lipidoid formulation [LLF] in the following) as described by Jarzębi nska et al 35 The liver specificity of LLF was first confirmed in a formulation with firefly luciferase cmRNA. A 1 mg/kg dose of this formulation was administered intravenously to mice and luciferase protein activity was measured 6 hr after administration.…”
Section: Ace2 Cmrna Can Be Selectively Targeted To the Liver And Lungmentioning
confidence: 99%
See 2 more Smart Citations
“…Other research has also reported on the optimization of cation structure in polyplexes and lipoplexes, showing that properties of cations, such as charge density, charge number, and pH-dependent protonation largely determined the chemical and biological properties of the carriers, including nucleic acid compaction status, nuclease tolerability, and endosomal escaping capability. [49][50][51][52][53][54][55] The dissociation of nucleic acid carriers through interaction with GAGs or other molecules is another critical problem for in vivo nucleic acid delivery, and crosslinking the polymers or lipids comprising the carriers is an effective solution to this problem. However, after reaching the cytosol or nuclei of target cells, pDNA and mRNA in the carriers should be released to allow efficient transcription or translation.…”
Section: Introductionmentioning
confidence: 99%